Exploring Politeness: Analyzing the Arabic Translation In Jane Austen's Sense And Sensibility - Mahmoudi, Mariem; Chirig, Abdelkrim (International Journal of Linguistics and Translation Studies, 2023)
Research shows that the concept of politeness is inherently intricate. The current paper examines the role of politeness in translation and highlights its significance as a chief aspect for translators. It focuses on the relationship between pragmatics and translation. The study analyzes the Arabic translation of selected chapters from Jane Austen's Sense and Sensibility, which takes place during the Victorian era and employs various linguistic elements that depict many aspects of politeness. The analysis discusses honorific titles and politeness expressions in both the source English text and its Arabic translation. Following a qualitative approach, Roger T. Bell's discourse parameters are implemented as the analytical framework. Through this examination, the paper highlights the relationship between translation and pragmatics while enhancing our understanding of cross-cultural linguistic differences. The results show that neglecting pragmatic features in translation (i.e., politeness) often due to specific factors can result in incomplete or poor translations, potentially altering the formality of the text unintentionally.